BEYOND ROTE LEARNING: USING CONSTRUCTIVIST APPROACH TO ENHANCE GRAMMAR COMPREHENSION AND APPLICATION IN ENGLISH WRITING - Tazeen, Aliya; Kader, Noora Abdul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The shift from conventional teaching methods to learner-centric approaches reflects the changing landscape of education towards more individualised and engaging learning experiences. Constructivism is a creative approach that is one of the best methods for improving English language proficiency. It is a well-known learner-centric method emphasising active participation, inquiry, and knowledge-building in interactive, discussion-based learning settings. The National Education Policy (2020) also supports a pedagogical framework that focuses on the student and encourages experiential learning, holistic growth, inquiry-based investigation, and adaptable teaching methodologies. This study examines the efficacy of authentic teaching practices rooted in the constructivist approach to teaching grammar in secondary schools. This study supports the NEP’s goal of using constructivist, learner-centric techniques to transform education. The research design employed is quasi-experimental. Data is gathered from two intact classes of the ninth grade, comprising around 80 students from Aligarh Muslim University. The control and experimental groups consist of 40 participants each, ensuring equal sample sizes in both groups. The sample is chosen using the convenient sampling method, and the data is analysed using suitable statistical techniques such as t-tests and ANCOVA. The study results will be used to modify and reorganise instructional strategies so students acquire grammatical structures more successfully.